Immunopathogenesis of genital Chlamydia infection: insights from mouse models. Issue 4 (4th February 2021) - Dockterman, Jacob; Coers, Jörn
ABSTRACT: Chlamydiae are pathogenic intracellular bacteria that cause a wide variety of diseases throughout the globe, affecting the eye, lung, coronary arteries and female genital tract. Rather than by direct cellular toxicity, Chlamydia infection generally causes pathology by inducing fibrosis and scarring that is largely mediated by host inflammation. While a robust immune response is required for clearance of the infection, certain elements of that immune response may also damage infected tissue, leading to, in the case of female genital infection, disease sequelae such as pelvic inflammatory disease, infertility and ectopic pregnancy. It has become increasingly clear that the components of the immune system that destroy bacteria and those that cause pathology only partially overlap. In the ongoing quest for a vaccine that prevents Chlamydia -induced disease, it is important to target mechanisms that can achieve protective immunity while preventing mechanisms that damage tissue. This review focuses on mouse models of genital Chlamydia infection and synthesizes recent studies to generate a comprehensive model for immunity in the murine female genital tract, clarifying the respective contributions of various branches of innate and adaptive immunity to both host protection and pathogenic genital scarring. Abstract : This review summarizes mouse model studies that significantly contributed to our current understanding of the protective and pathogenic immune responses taking place during genital Chlamydia infections.